„Racjonalne usprawnienie” w ramach edukacji dzieci i młodzieży z niepełnosprawnością – rozważania na kanwie konwencji o prawach osób niepełnosprawnych Część 2 - Mikrut, Adam (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The authorities of the Republic of Poland have ratified the Convention on the Rights of Persons with Disabilities and have undertaken the responsibility to implement such changes in the internal law and in social policy which aim at ensuring full and equal enjoyment of all rights and freedoms by people with disabilities and preventing their discrimination in different aspects of life. One of the ways of fulfilling this commitment is described as ‘reasonable accommodation’. The author of this article has attempted to find manifestations of such activities in the field of school legislation and its practical examples. As a result, it turned out that in the analysed area many solutions are in line with the spirit of the ‘reasonable accommodation’.